Den store Ånd eller de små spøgelser – om kapitalismens legitimerende narrativer - Beck Holm, Andreas (Slagmark - Tidsskrift for idéhistorie, 2018)
THE GREAT SPIRIT OR THE LITTLE GHOSTS? ON THE LEGITIMIZING NARRATIVES OF CAPITALISM Boltanski and Chiapello’s The New Spirit of Capitalism is a monumental work that diagnoses the nature of contemporary network capitalism and gives a compelling statement of a new ideology that sustains and legitimizes capitalism as an economic system. This paper, however, aims to raise a number of objections to Boltanski and Chiapello’s approach. It questions partly whether the ideology they identify is actually capable of legitimizing contemporary capitalism, partly whether it may not be more constructive to abandon the search for one ‘spirit of capitalism’ in favor of identifying a system of different ideologies that all serve as legitimizing narratives. The paper identifies business ethics as one such ideology and argues that it actually outperforms the one identified by Boltanski and Chiapello according to the criteria defined by the authors themselves. Finally, it is argued that the different ideologies, despite their discrepancies, share one defining characteristic: They are all incapable of making a case for capitalism as an economic system that guarantees the contemporary workforce social security, and that reflects the reality of capitalist society today.